2020
DOI: 10.3390/brainsci10050262
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Receptor DRD2 Gene rs1076560, Personality Traits and Anxiety in the Polysubstance Use Disorder

Abstract: Development of an addiction is conditioned by many factors. The dopaminergic system has been shown to be the key element in this process. In this paper, we analyzed the influence of dopamine receptor 2 polymorphism rs1076560 in two groups—polysubstance-dependent male patients (n = 299) and the controls matched for age (n = 301). In both groups, we applied the same questionnaires for testing—Mini-international neuropsychiatric interview, the NEO Five-Factor Inventory, and the State–Trait Anxiety Inventory. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Additionally, within this same block, the rs1076560 T allele has been associated with responsiveness to anti-psychotic medications [ 36 ] and reduction in symptomatology in pharmacologic treatment of Parkinson’s Disease [ 37 ], but was most recently demonstrated to be associated with the personality characteristics of neuroticism and anxiety in polysubstance dependent males [ 38 ]. However, other studies have not found an association for this variant and substance use disorder [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, within this same block, the rs1076560 T allele has been associated with responsiveness to anti-psychotic medications [ 36 ] and reduction in symptomatology in pharmacologic treatment of Parkinson’s Disease [ 37 ], but was most recently demonstrated to be associated with the personality characteristics of neuroticism and anxiety in polysubstance dependent males [ 38 ]. However, other studies have not found an association for this variant and substance use disorder [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most interesting gene is DRD2; despite mixed results among candidate-gene association studies, with positive association ( Wacker et al ., 2005 ; Jutras-Aswad et al ., 2012 ; Grzywacz et al ., 2020 ; Suchanecka et al ., 2020 ) outweighing the null hypothesis ( Hibino et al ., 2006 ; Pełka-Wysiecka et al ., 2012 ), GWAS studies replicated several times the finding of its association with neuroticism ( Okbay et al ., 2016 ; Luciano et al ., 2018 ; Nagel et al ., 2018 , 2020 ; Turley et al ., 2018 ; Hill et al ., 2020 ). As mentioned previously, the DRD2 gene codes for a crucial dopamine receptor, currently regarded as being one of the main target of antipsychotics medications.…”
Section: Discussionmentioning
confidence: 99%
“…Other research studies showed that the combination of two highly prevalent DRD2 SNPs, rs6276 and rs6277, decreased the expression of DRD2 as a consequence of a diminished DRD2 mRNA, and moreover, a decreased D2R receptor availability and affinity [ 70 , 72 , 162 , 163 , 164 , 165 ]. Han et al found that these combined effects of DRD2 and SNPs also diminished the levels of phosphorylated β-catenin, presumably causing more β-catenin to be successfully degraded, and in this way, the transcription of the Wnt/β-catenin pathway of the target genes was stimulated.…”
Section: Discussionmentioning
confidence: 99%